2015
DOI: 10.3390/jcm4091774
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic Obesity in Craniopharyngioma Patients: Disturbed Energy Homeostasis Related to Extent of Hypothalamic Damage and Its Implication for Obesity Intervention

Abstract: Hypothalamic obesity (HO) occurs in patients with tumors and lesions in the medial hypothalamic region. Hypothalamic dysfunction can lead to hyperinsulinemia and leptin resistance. This review is focused on HO caused by craniopharyngiomas (CP), which are the most common childhood brain tumors of nonglial origin. Despite excellent overall survival rates, CP patients have substantially reduced quality of life because of significant long-term sequelae, notably severe obesity in about 50% of patients, leading to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 181 publications
(274 reference statements)
6
49
0
Order By: Relevance
“…Damage to the arcuate nucleus, resulting in leptin resistance and hyperinsulinaemia, is thought to result in hyperphagia; leptin supplementation is not a therapeutic option for these patients, but recent trials have included strategies to reduce insulin secretion (see below and Table ). There are multiple reasons for reduced energy expenditure in CP, including visual and neurological disability, somnolence, reduced sympathetic tone, and deconditioning from obesity, the identification of which may provide a therapeutic target . Excessive energy storage mediated by hyperinsulinism may be targeted with pharmaceutical interventions or with metabolic surgery .…”
Section: Obesitymentioning
confidence: 99%
See 2 more Smart Citations
“…Damage to the arcuate nucleus, resulting in leptin resistance and hyperinsulinaemia, is thought to result in hyperphagia; leptin supplementation is not a therapeutic option for these patients, but recent trials have included strategies to reduce insulin secretion (see below and Table ). There are multiple reasons for reduced energy expenditure in CP, including visual and neurological disability, somnolence, reduced sympathetic tone, and deconditioning from obesity, the identification of which may provide a therapeutic target . Excessive energy storage mediated by hyperinsulinism may be targeted with pharmaceutical interventions or with metabolic surgery .…”
Section: Obesitymentioning
confidence: 99%
“…The impact of radiotherapy on long‐term weight gain must also be considered; one study has shown a detrimental effect of radiotherapy on physical activity . Weight gain is particularly rapid in the first year after surgery . A description of the function of hypothalamic nuclei in energy balance, which may be damaged by tumour bulk or surgical insult, is provided in Table with a cartoon description in Figure and is reviewed in detail by Roth …”
Section: Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…Although 12–19% of affected patients are already obese at diagnosis, the most rapid, uncontrollable weight gain usually occurs during the first 6–12 months following neurosurgical intervention [6]. Adding to the well-established characteristics of hypothalamic obesity, extremely obese craniopharyngioma patients typically suffer from panhypopituitarism and demonstrate significant hyperleptinemia due to anatomic leptin resistance, inadequate hyperinsulinemia for their degree of obesity, impaired incretin response, and reduced levels of blood catecholamines and urinary metabolites, and α-MSH [5, 7, 8]. …”
Section: Introductionmentioning
confidence: 99%
“…The hypothalamus regulates glucose metabolism through parasympathetic activity. Hypothalamic damage, mainly due to brain tumour, may result in upregulation of parasympathetic activity resulting in hyperinsulinemia [199]. Often, obesity is associated with hyperinsulinemia, both under fasting conditions and post-prandially.…”
Section: Somatostatin and Obesitymentioning
confidence: 99%